2021
DOI: 10.3390/su132111594
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policy Uncertainty, Financial Expenditure and Energy Poverty: Evidence Based on a Panel Threshold Model

Abstract: The COVID-19 pandemic has forced people to pay more attention to the negative impacts of economic policy uncertainty on energy poverty. Meanwhile, through financial expenditure, governments might play a critical role in energy poverty alleviation, but there is little focus on this factor in the literature. We employ a panel threshold model to investigate the threshold effect of economic policy uncertainty between financial expenditure and energy poverty. This model can keenly explore the time-varying character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…However, there are differences with respect to taxes. This is in line with the findings of Che and Jiang [49] and Nagaj [86] that government financial spending has a significant positive impact on alleviating fuel poverty. Similar to Fragkos et al [72], it was also found that taxes imposed on energy products can increase the risk of fuel poverty.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, there are differences with respect to taxes. This is in line with the findings of Che and Jiang [49] and Nagaj [86] that government financial spending has a significant positive impact on alleviating fuel poverty. Similar to Fragkos et al [72], it was also found that taxes imposed on energy products can increase the risk of fuel poverty.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, in the context of studying fuel poverty, the share of energy from renewable sources is an important factor. In addition, the literature indicates [49,72,73] that energy and climate policies themselves can affect citizens' incomes, just as economic prosperity affects the amount of energy consumed and the environmental impact of sectors [84]. For this reason, when establishing a list of independent variables affecting fuel poverty, it is important to keep in mind the interdependence between factors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result highlights the need for more attention to public expenditure composition and energy poverty in future research studies. More recently, the empirical literature has emphasized the negative impact of economic uncertainty on various economic factors such as investment, economic growth, unemployment, and monetary and fiscal policy orientations (Xiahui and Minxing 2021 ; Siksnelyte-Butkiene 2022 ). As a potential future perspective, this work should focus on the role of global economic uncertainty in the dynamics of energy poverty and the influence of public expenditure.…”
Section: Discussionmentioning
confidence: 99%